The Effectiveness of the STAD Cooperative Learning Model in Enhancing Students’ Conceptual Understanding in Biology at Senior High School Level - Puspitasari, Dyah Ayu; Fatikhah, Nurul (Universitas Pakuan, 2023)
This study aims to examine the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving students’ conceptual understanding of biology at the senior high school level. The research was conducted at SMA Negeri 1 Tempel, Yogyakarta, Indonesia, using a quasi-experimental design with a one-group pretest–posttest approach. A total of 32 students from class X MIA 2 participated in the study. Data were collected using multiple-choice tests administered through the Quizizz platform to measure students’ comprehension before and after the implementation of the STAD model. The normalized gain score analysis showed an average value of 0.407, indicating a medium level of effectiveness. Statistical testing using a single mean Z-test confirmed that the posttest results significantly improved compared to the pretest. The findings demonstrate that the STAD cooperative learning model promotes active participation, collaboration, and critical thinking among students, leading to better conceptual mastery. This research highlights the pedagogical value of cooperative learning strategies such as STAD in fostering meaningful and engaging science learning experiences in secondary education.